2021
DOI: 10.3390/insects12060534
|View full text |Cite
|
Sign up to set email alerts
|

Species Identification of Wireworms (Agriotes spp.; Coleoptera: Elateridae) of Agricultural Importance in Europe: A New “Horizontal Identification Table”

Abstract: Wireworms are yellowish soil-dwelling larvae that damage a wide range of arable crops. The most common wireworms found in European cultivated fields (except for the Caucasus) belong to the genus Agriotes (Coleoptera: Elateridae). In several European countries, environment-impacting insecticides are applied on a prophylactic basis to control them. However, before any treatment can be applied, European legislation requires that an assessment is done when pest population levels exceed a damage threshold. The thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…Wireworms can cause 100% crop damage when infestation occurs during the seedling stage, leading to poor crop stands 64 . Studies in North America and Europe have identified numerous wireworm species with devastating effects on a broad range of crops 62 , 68 , 71 . However, the larvae of most sub-Saharan species remain undescribed, with no DNA sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…Wireworms can cause 100% crop damage when infestation occurs during the seedling stage, leading to poor crop stands 64 . Studies in North America and Europe have identified numerous wireworm species with devastating effects on a broad range of crops 62 , 68 , 71 . However, the larvae of most sub-Saharan species remain undescribed, with no DNA sequence data.…”
Section: Discussionmentioning
confidence: 99%
“…The collected larvae were brought individually to the laboratory in plastic containers (50 mL) containing autoclaved sandy loamy soil (20 g) with a slice of potato (Ø2 cm) and kept at 25 °C. The 4th and 5th larvae were separated according to their head width and observed for one week for any sign of infection [ 9 , 34 , 35 ]. Only healthy larvae were included in the pathogenicity bioassays.…”
Section: Methodsmentioning
confidence: 99%
“…Up to now, more than 39 wireworm species have been reported to attack potatoes around the world [ 7 ]. However, 9 species, Agriotes brevis Candèze, Agriotes lineatus Linnaeus, Agriotes litigiosus Rossi, Agriotes obscurus Linnaeus, Agriotes proximus Linnaeus, Agriotes rufipalpis Brullé, Agriotes sordidus Illiger, Agriotes sputator Linnaeus, and Agriotes ustulatus Schäller, are considered the most devastating in Europe [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The plants were exposed to artificial light from high pressure sodium vapour light (Osram) for four hours daily, and were watered every four days with tap water. Fifty wireworms (A. lineatus) were collected from soil on the Biotechnical Faculty grounds and identified using the raster pattern on the lower side of their abdomen, according to Furlan et al [33]. Ten growing pots were randomly chosen for wireworm infestation (five larvae per pot), while the remaining ten pots were used as controls.…”
Section: Glasshouse Experimentsmentioning
confidence: 99%